Synchronization and blind detect algorithm for dual channel audio watermark - FENG Tao1; HAN Ji-qing1 (Tongxin xuebao)
A synchronization and a blind detect algorithm based on character of dual-channel audio was presented by calculating Mel frequency spectrum coefficient and using correlation between left and right channel,the synchronized segment was fix on and the performance was analyzed.After the watermarking was embedded into synchronized segment in both channels at the same time,it could be detected without original audio and watermarking information by calculat-ing the correlation of them between left and right channels.Experimental results show that the proposed approach can significantly improve the watermarking robustness under the attacks of adding noise,MP3 compression,resample and requantization.